Going with the Flow: Multiscale Insights into the Composite Nature of Water Transport in Roots. Issue 4 (26th October 2018) - Couvreur, Valentin; Faget, Marc; Lobet, Guillaume; Javaux, Mathieu; Chaumont, François; Draye, Xavier
Abstract : A bio-physical model of the "root hydraulic anatomy" allows testing hypotheses related to radial water transport down to the cell level and proves complementary to current experimental approaches. Abstract: As water often limits crop production, a more complete understanding of plant water capture and transport is necessary. Here, we developed MECHA, a mathematical model that computes the flow of water across the root at the scale of walls, membranes, and plasmodesmata of individual cells, and used it to test hypotheses related to root water transport in maize ( Zea mays ). The model uses detailed root anatomical descriptions and a minimal set of experimental cell properties, including the conductivity of plasma membranes, cell walls, and plasmodesmata, which yield quantitative and scale-consistent estimations of water pathways and root radial hydraulic conductivity ( k  r ). MECHA revealed that the mainstream hydraulic theories derived independently at the cell and root segment scales are compatible only if osmotic potentials within the apoplastic domains are uniform. The results suggested that the convection-diffusion of apoplastic solutes explained most of the offset between estimated k  r in pressure clamp and osmotic experiments, while the contribution of water-filled intercellular spaces was limited. Furthermore, sensitivity analyses quantified the relative impact of cortex and endodermis cell conductivity of plasma membranes on root k  r and suggested that only the latter contributed substantially to k  r due to the composite nature of water flow across roots. The explicit root hydraulic anatomy framework brings insights into contradictory interpretations of experiments from the literature and suggests experiments to efficiently address questions pertaining to root water relations. Its scale consistency opens avenues for cross-scale communication in the world of root hydraulics.